2014
DOI: 10.1603/ec13315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tetraploid Switchgrass (Poales: Poaceae) Populations for Host Suitability and Differential Resistance to Four Cereal Aphids

Abstract: Switchgrass, Panicum virgatum L., is being developed as a bioenergy feedstock. The potential for large-scale production has encouraged its evaluation as a host for important grass pests. Eight no-choice studies were performed for two developmental stages of two switchgrass cultivars ('Kanlow' and'Summer') and two experimental strains, K x S, and S x K produced by reciprocal mating of these cultivars followed by selection for high yield. Plants were evaluated for host suitability and damage differences to herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Plants were grown to the V-1 stage [23] in Cone-tainers essentially as described earlier [19]. Each Cone-tainer had a single plant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants were grown to the V-1 stage [23] in Cone-tainers essentially as described earlier [19]. Each Cone-tainer had a single plant.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts were made to condition aphids on the same switchgrass population and developmental stage they were to be tested on for at least 1 week; however, efforts to condition enough of either aphid species on Kanlow were unsuccessful. As a result, all aphids were conditioned for at least 1 week prior to the beginning of each study on Summer, which had preliminarily been identified as the susceptible population [19], in the V-1 stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of these cultivars and experimental strain has been published [26,27]. The experimental strain was developed by Dr. Kenneth Vogel, USDA-ARS (retired), Lincoln, NE, who also provided seeds of the cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Koch et al [26,27] have shown that tetraploid switchgrasses can serve as suitable hosts for two different aphids, namely the greenbug, Schizaphis graminum (Rondani), and the yellow sugarcane aphid, Sipha flava (Forbes). Both aphids can be found across the USA and have been well characterized as pests of many cultivated and native grasses [6,7,24,31].…”
Section: Introductionmentioning
confidence: 99%